Pengaruh Kreativitas, Berpikir Kritis, dan Proses Pembelajaran Terhadap Hasil Belajar Mata Pelajaran Ekonomi Kelas XI IPS SMA Negeri 6 Surakarta Tahun Pelajaran 2018/2019 - Chania Hasna Afifah; Trisno Martono; Sudarno sudarno (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2023)
This study aims to determine whether or not there is (1) the effect of creativity on the learning process in Economics Class XI IPS subjects in SMA Negeri 6 Surakarta, (2) the influence of critical thinking on the learning process in Economics Class XI IPS subjects at SMA Negeri 6 Surakarta, (3 ) the effect of creativity on learning outcomes in Economics Class XI IPS subjects in SMA Negeri 6 Surakarta, (4) the influence of critical thinking on learning outcomes in Economics Class XI IPS subjects in SMA Negeri 6 Surakarta. (5) the effect of the learning process on learning outcomes in Economics XI IPS subjects in SMA Negeri 6 Surakarta.The method used in this research is descriptive quantitative research method. The population in this study amounted to 175 students of class XI IPS in SMA Negeri 6 Surakarta. The sample in this study amounted to 117 students with the sampling technique used was proportional random sampling. Data collection was carried out using a questionnaire technique. The data analysis technique used is the analysis prerequisite test using SPSS version 23.0 and to test the hypothesis with path analysis using Lisrell 8.80.Based on the results of the study it can be concluded that (1) creativity directly affects the learning process by 71%, (2) critical thinking directly influences the learning process by 20%, (3) creativity directly influences the learning outcomes 25%, (4 ) critical thinking directly affects the learning outcomes of 21%, (5) the learning process directly affects the learning outcomes of 62%.